Notary's Obligation to Provide Legal Services Free of Charge - Indrajaya, Rosy (Jurnal Cakrawala Hukum, 2023)
The problem in this study is related to the parameter of the phrase unable to fulfill the Notary's obligations regulated in the Notary Office Law and the form of legal protection. So that the goal of this writing is to get legal protection for Notaries against the ambiguity of legal norms. This study uses normative legal research methods with several approaches, namely the statutory approach and the conceptual approach. The results of this study indicate that preventive legal protection can be provided through laws and regulations that explain the criteria/standards for underprivileged people, namely: livelihood, salary or wages, those who are only able to meet basic needs that are decent but unable to pay contributions for themselves and his family. The repressive legal protection that can be given to a Notary, in this case, is if the Notary is not sure about the financial condition of the apparel so that he cannot provide legal services in the notary field for free, then another form of providing legal services is in the form of a reduction in honorarium or notary fees. in making a deed, the amount of the notary's honorarium has been determined by the provisions of the law. How to cite item: Indrajaya, Rosy, â€œNotary's Obligation to Provide Legal Services Free of Charge.â€ Jurnal Cakrawala Hukum14 no. 1 (2023): 106-114. DOI: 10.26905/idjch.v14i1.8516.